Genomic and Fitness Consequences of Genetic Rescue in Wild Populations - Fitzpatric, Sarah W. (2020)
Gene flow is an enigmatic evolutionary force because it can limit adaptation but may also rescue small populations from inbreeding depression [1, 2, 3]. Several iconic examples of genetic rescue—increased population growth caused by gene flow [4, 5]—have reversed population declines [6, 7]. However, concerns about outbreeding depression and maladaptive gene flow limit the use of human-mediated gene flow in conservation [8, 9]. Rescue effects of immigration through demographic and/or genetic mechanisms have received theoretical and empirical support, but studies that monitor initial and long-term effects of gene flow on individuals and populations in the wild are lacking. Here, we used individual-based mark-recapture, multigenerational pedigrees, and genomics to test the demographic and evolutionary consequences of manipulating gene flow in two isolated, wild Trinidadian guppy populations. Recipient and source populations originated from environments with different predation, flow, and resource regimes [10]. We documented 10-fold increases in population size following gene flow and found that, on average, hybrids lived longer and reproduced more than residents and immigrants. Despite overall genomic homogenization, alleles potentially associated with local adaptation were not entirely swamped by gene flow. Our results suggest that genetic rescue was caused not just by increasing individual genetic diversity, rather new genomic variation from immigrants combined with alleles from the recipient population resulted in highly fit hybrids and subsequent increases in population size. Contrary to the classic view of maladaptive gene flow, our study reveals conditions under which immigration can produce long-term fitness benefits in small populations without entirely swamping adaptive variation.